Virtual reconstruction of endocast anatomy in early ray-finned fishes (Osteichthyes, Actinopterygii). (July 2014) - Giles, Sam; Friedman, Matt
Abstract : Cranial endocasts, infillings of the skeletal void that once contained the brain and associated soft tissues, represent detailed anatomical structures that have long been the focus of paleontological investigation. We applied computed tomographics (CTs) in order to generate endocast models for the Paleozoic actinopterygian fishes Mimipiscis and Kentuckia, which serve as key representatives of anatomically primitive, early ray fins in analyses of early vertebrate relationships. The resultant endocranial models generally corroborate existing accounts of endocranial anatomy in these genera, drawn from descriptions of the inner face of the brain cavity. However, the endocasts also provide new anatomical details, the most significant of which are the presence in Mimipiscis of widely divergent olfactory tracts, small optic lobes, and anterior and posterior semicircular canals that extend dorsal to the roof of the endocranial chamber. By contrast, Kentuckia possesses a single, straight olfactory tract, wide optic lobes, and anterior and posterior semicircular canals that do not reach the dorsal surface of the endocast. In each of these features, Kentuckia resembles stratigraphically younger actinopterygians such as Lawrenciella and Kansasiella, whereas Mimipiscis more closely resembles sarcopterygians and other outgroups. This character distribution provides further support for earlier phylogenetic interpretations of these genera.